THE INCREASING OF WRITING SKILLS FOR THE VISUAL IMPAIRMENT THROUGH USE OF CBM (CURRICULUM BASED MEASUREMENT) - Fandi Pradana Priambodo; Endro Wahyuno (Department of Special Education, 2016)
This study examined the writing skills of visual impairment when Y (initials) experienced some errors in writting some diction words by the teacher, Y reduced, replaced or even eliminated letters that should has been written.This research used a quantitative approach of Single Subject Research (SSR) with design of multiple baseline cross variables. The results of this research showed that CBM (Curriculum Based Measurement) can increase to be effectivelly the writing skills of students with visual impairment in SDLB.